The Three Sisters Based on a Play by Anton Chekhov - Olivier, Laurence; Unsworth, Geoffrey; Heard, Daphne; Jacobi, Derek; Plowright, Joan (Fremantle Media, 2005)
The four plays written by Anton Chekhov just before his death in 1904, "The Seagull", "Three Sisters", "Uncle Vanya" and "The Cherry Orchard", are among the most important and influential works of drama – the rich, complex inner lives of their characters being the perfect conduit for the modern drama techniques of Stanislavsky. Laurence Olivier's work at the National Theatre in the late sixties wields a similar authority and has made an indelible stamp - for better or worse - on the direction and the stature of British theatre. The American Film Theatre therefore scored quite a coup in capturing the film version of Olivier's National Theatre stage production of one of the most influential plays in modern drama. [www.dvdtimes.co.uk]